A systematic review and meta-analysis of the association between cardiovascular health determined by life's essential 8 and risk of mortality and major non-communicable diseases - Li, Guangkai; Zhang, Yanfang; Wu, Qingxu; Shi, Beibei; Chen, Dexu (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesThis study aimed to explore the associations between cardiovascular health (CVH) and the risk of mortality and major non-communicable diseases by conducting a meta-analysis.MethodsSeveral databases including Pubmed, Embase, Web of science, Scopus were searched for studies exploring the prospective associations between ideal CVH and health outcomes compared with the poor CVH status and published up to January 20, 2025. Adjusted relative risks (RRs) were used to calculate pooled effect size using random-effect models.ResultsThis study included a total of 46 eligible studies. When comparing the ideal CVH score category to the poor CVH score category, the pooled RRs were 0.44 (95% CI: 0.40–0.48) for all-cause mortality, 0.33 (95% CI: 0.29–0.39) for CVD mortality, 0.51 (95% CI: 0.46–0.57) for total cancer mortality, 0.36 (95% CI: 0.33–0.39) for CVD, 0.75 (95% CI: 0.69–0.81) for total cancer and 0.65(95% CI: 0.55–0.96) for all-cause dementia, respectively. We also observed significant reduction of risk of diabetes, NAFLD, depression, anxiety, chronic kidney diseases, etc. Due to limited literatures and high heterogeneity, some of these results required further validation. Dose-response meta-analysis showed a linear reduction in the risk of all-cause mortality, total cancer mortality and a nonlinear reduction of CVD mortality and incident stroke, myocardial infarction.ConclusionsThis study finds that ideal CVH score is strongly inversely associated with the risk of all-cause, CVD and total cancer mortality, as well as incident several common NCDs. There's a linear dose-response reduction of risk of all-cause mortality, total cancer mortality and a nonlinear dose-response reduction of risk of CVD mortality, incident CVD, stroke, myocardial infarction with the increase of CVH score.Systematic Review RegistrationPROSPERO, identifier CRD42024494354.